A low-dose cytarabine, aclarubicin and granulocyte colony-stimulating factor priming regimen versus a daunorubicin plus cytarabine regimen as induction therapy for older patients with acute myeloid leukemia: A propensity score analysis. (March 2016) - Minakata, Daisuke; Fujiwara, Shin-ichiro; Ito, Shoko; Mashima, Kiyomi; Umino, Kento; Nakano, Hirofumi; Kawasaki, Yasufumi; Sugimoto, Miyuki; Yamasaki, Ryoko; Yamamoto, Chihiro; Ashizawa, Masahiro; Hatano, Kaoru; et al.
Highlights: We compared the efficacy of the DNR-AraC regimen to that of the CAG regimen. We calculated the propensity score for selecting the CAG regimen. We compared the two groups after stratification according to the propensity score. Intensive induction therapy should be performed for fit elderly patients with AML. Less-intensive therapy is sufficient for patients with higher age, MRC, lower WBC. Abstract: This retrospective analysis compared the efficacy of intensive induction therapy consisting of daunorubicin and cytarabine (DNR-AraC) to that of less-intensive therapy including low-dose cytarabine, aclarubicin and granulocyte colony-stimulating factor priming (CAG). Patients aged 60 years or older who were newly diagnosed as acute myeloid leukemia (AML) were analyzed. Sixty-four and 48 patients were treated with DNR-AraC and CAG, respectively. The complete remission rates, 3-year overall survival and event-free survival in the DNR-AraC group were significantly superior to those in the CAG group (65.6% vs. 29.2%, p  < 0.001, 38.4% vs. 12.3%, p  = 0.0033, and 20.3% vs. 7.8%, p  = 0.0030, respectively), although these differences were not statistically significant in multivariate analyses. Next, we calculated a propensity score for selecting the CAG regimen from six factors. The DNR-AraC regimen was associated with better survival than the CAG regimen in a low propensity score group, but there was no difference in survival between regimens in a high propensity score group. Intensive therapy should be performed for patients with sufficient general and comorbid conditions, but less-intensive therapy may be sufficient for patients with higher age, myelodysplasia-related changes, and lower white blood cell counts, which were relevant factors in the propensity score calculation.